The forgotten Piers Plowman : early Tudor Plowman texts - Thijms, Annemarie (Trinity College (Dublin, Ireland). School of English, 2007)
Methods: This thesis combines textual analysis with research into the historical, religious and literary context of early Tudor Ploughman texts, looking back to the late fourteenth century ploughman literature. In chapter one I discuss the text Of Gentylnes and Nobylyte and the concept of gentility in relation to the three social classes. In addition, I examine the enclosure movement in early Tudor literature, mainly focussing on A Proper Dyaloge betwene a Gentilman and an Husbandman and Pyers Plowmans Exhortation, placing them in their literary and political context. In chapter two I examine the doctrine of transubstantiation in the early Tudor ploughman texts The Banckett of Johan the Reve unto Peirs Ploughman, Luke Shepherd's John Bon and Mast Parson, and A Godly Dyalogue and Dysputacyion Betwene Pyers Plowman and a Popysh Preest, again placing them in their historical and religious framework. In chapter three I examine the relationship between the priest and the ploughman. In chapter four I discuss the figure of the ploughman. In the final chapter I answer the question why the figure of the ploughman was so popular. In the appendix I have transcribed The Banckett from its manuscript source.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin